2013
DOI: 10.1142/s1793604713500628
|View full text |Cite
|
Sign up to set email alerts
|

GRAPHENE/MULTI-WALLED CARBON NANOTUBE COMPOSITE AS AN EFFECTIVE SUPPORTS TO ENHANCE THE PHOTOCATALYTIC PROPERTY OF Cu-DOPED ZnO NANOPARTICLES

Abstract: In this paper, graphene/multi-walled carbon nanotubes (GM) hybrid nanostructure was synthesized by modifying GR using salicylamide. Cu -doped ZnO nanoparticles were successfully decorated on GR/MWNTs hybrids (GM). Their photocatalytic performance for the degradation of methyl orange (MO) was investigated and the results showed that the synthetic GM/ Cu -doped ZnO hybrids exhibited better photocatalytic ability than MWNTs/ Cu -doped ZnO and GR/ Cu -doped ZnO hybrids, in which the degraded rate for 20 mg/L MO so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Zhou et al reported that reduced graphene oxide enhanced the photocatalytic degradation of ZnO for ethylene blue [23]. Herring et al reported a simple one-step synthesis of ZnO nanopyramids supported on reduced graphene oxide nanosheets, and the ZnO-reduced graphene oxide nanocomposites showed an enhanced photocatalytic activity for the degradation of the dye over the unsupported ZnO nanopyramids [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al reported that reduced graphene oxide enhanced the photocatalytic degradation of ZnO for ethylene blue [23]. Herring et al reported a simple one-step synthesis of ZnO nanopyramids supported on reduced graphene oxide nanosheets, and the ZnO-reduced graphene oxide nanocomposites showed an enhanced photocatalytic activity for the degradation of the dye over the unsupported ZnO nanopyramids [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…When Ag 2 O is introduced into CaAlONS to form Ag 2 O-CAONCS, Ag 2 O-CAONCS exhibits a sharper decrease in the intensity of the PL peak than CaAlONS. Therefore, Ag 2 O-CAONCS exhibits fast charge transfer and enhanced separation of photo-generated carriers at the interface between Ca 5 Al 6 O 14 and Ag 2 O, which will decrease the recombination efficiency of carriers and enhance the catalytic performance [34,35].
Figure 6 PL Spectra of the CaAlONS, 0.1-Ag 2 O-CAONCS.
…”
Section: Resultsmentioning
confidence: 99%
“…Single component photocatalysts have the limitations of absorption spectrum, oxidation, and reduction ability, separation of photo-generated charge carriers. Metal doping is efficient for enhancing photocatalytic performance of photocatalysts by decreasing band gap, recombination of electronhole pairs and improving redox ability [12,13]. It is well known that Ag is an efficient doping element for improving photocatalytic performance of photocatalysts [14].…”
Section: Introductionmentioning
confidence: 99%